Optimised CO2-containing medium for in vitro culture and transportation of mouse preimplantation embryos without CO2 incubator. - Yasuyuki Kikuchi; Sayaka Wakayama; Daiyu Ito; Masatoshi Ooga; Teruhiko Wakayama (PLoS ONE, 2021)
Conventional in vitro culture and manipulation of mouse embryos require a CO2 incubator, which not only increases the cost of performing experiments but also hampers the transport of embryos to the other laboratories. In this study, we established and tested a new CO2 incubator-free embryo culture system and transported embryos using this system. Using an Anaero pouch, which is a CO2 gas-generating agent, to increase the CO2 partial pressure of CZB medium to 4%-5%, 2-cell embryos were cultured to the blastocyst stage in a sealed tube without a CO2 incubator at 37°C. Further, the developmental rate to blastocyst and full-term development after embryo transfer were comparable with those of usual culture method using a CO2 incubator (blastocyst rate: 97% versus 95%, respectively; offspring rate: 30% versus 35%, respectively). Furthermore, using a thermal bottle, embryos were reliably cultured using this system for up to 2 days at room temperature, and live offspring were obtained from embryos transported in this simple and very low-cost manner without reducing the offspring rate (thermal bottle: 26.2% versus CO2 incubator: 34.3%). This study demonstrates that CO2 incubators are not essential for embryo culture and transportation and that this system provides a useful, low-cost alternative for mouse embryo culture and manipulation.